2006
DOI: 10.1242/jcs.02786
|View full text |Cite
|
Sign up to set email alerts
|

Androgens modulate the inflammatory response during acute wound healing

Abstract: Impaired wound healing states in the elderly lead to substantial morbidity and mortality, and a cost to the health services of over $9 billion per annum. In addition to intrinsic ageing processes that per se cause delayed healing, studies have suggested marked differences in wound repair between the sexes. We have previously reported that, castration of male mice results in a striking acceleration of local cutaneous wound healing and dampens the associated inflammatory response. In this study, we report that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 59 publications
4
92
0
2
Order By: Relevance
“…However, there is also evidence suggesting that hyperinsulinemia drives androgen production (5). Irrespective of the cause, higher testosterone levels could drive inflammation (4,25). Given that adipocyte and muscle insulin resistance was observed only in male mice, we determined whether these defects were related to differences in testosterone levels.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is also evidence suggesting that hyperinsulinemia drives androgen production (5). Irrespective of the cause, higher testosterone levels could drive inflammation (4,25). Given that adipocyte and muscle insulin resistance was observed only in male mice, we determined whether these defects were related to differences in testosterone levels.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies by Ashcroft and colleagues, using surgical or chemical castration, have found that androgens were able to inhibit cutaneous wound healing, possibly by modulating inflammatory responses, matrix deposition, and keratinocyte function (1,(8)(9)(10). However, the in vivo role of androgens/AR signals in different cell types involved in the wound-healing process remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In males, testosterone and its more potent metabolite 5␣-dihydrotestosterone inhibit repair 1,4 ; in females, estrogens such as 17␤-estradiol accelerate healing. 5,6 Although the effects of estrogens on female cutaneous physiology are well characterized, their roles in males are poorly understood.…”
mentioning
confidence: 99%